Practical software configuration management the latenight developer's handbook - Mikkelsen, Tim (Software configuration management, 1997)
This book provides a quick, easy-to-read introduction to the advanced concept of configuration management. As software developers create new applications, they must map each step for later reference and quality checks -- like leaving behind a trail of bread crumbs. Written for individuals or small development teams who do not have vast resources and budgets, Mikkelson/Pherigo is a complete package of everything you need to create professional software.